Food cravings prospectively predict decreases in perceived self-regulatory success in dieting. (January 2017) - Meule, Adrian; Richard, Anna; Platte, Petra
Abstract: Food cravings are assumed to hamper dieting success, but most findings are based on cross-sectional studies. In the current study, female students were tested at the beginning of their first semester at university and six months later. They completed the Food Cravings Questionnaire-Trait-reduced (FCQ-T-r), the disinhibition subscale of the Eating Inventory, and the Perceived Self-Regulatory Success in Dieting Scale, and their height and weight were measured. Scores on the FCQ-T-r prospectively predicted higher disinhibition and lower perceived self-regulatory success in dieting after six months. Although FCQ-T-r scores did not predict increases in body mass index (BMI) directly, a serial mediation model revealed an indirect effect of FCQ-T-r scores at baseline on BMI after six months via increased disinhibition scores and decreased perceived self-regulatory success in dieting. To conclude, the current results provide evidence for a prospective relationship between trait food craving and decreases in dieting success. Furthermore, they suggest a possible mediator of this association (i.e., increases in disinhibited eating) as well as an indirect effect on body weight. Measurement of trait food craving may be a useful tool for predicting or monitoring treatment changes and relapse in eating- and weight disorders. Highlights: Female students were tested at the start of the first semester and six months later. Food cravings, disinhibited eating, and perceived dieting success were assessed. Food cravings at baseline prospectively predicted decreases in dieting success. Food cravings indirectly predicted increases in BMI via eating-related measures.